Methamphetamine abuse in Malaysia: an interpretive phenomenological perspective - Audi Azizul, Muhd Dhamir; Wan Jaafar, Wan Munira; Mohd Khir, Azlina; Amin, Samir Muhazzab (Human Resource Management Academic Research Society, 2023)
Southeast Asian countries including Malaysia play a major role in global drug trade and abuse. Use of amphetamine-type stimulants has increased in the past decade in Malaysia. Methamphetamines, known as "shabu," across much of Southeast Asia, have been on the rise for years and addiction specialists are running out of solutions. Therefore, this study intentions to explore the perspective and experience of Meth. clients who is undergoing a rehabilitation program at the Narcotic Addiction Rehabilitation Centre, Tampin, Melaka (Puspen Tampin, Melaka) through an interpretive phenomenological approach. This study was conducted through in-depth interviews with seven male informants in 2022. Clients' perspectives and experiences of their involvement in Meth abuse well documented through the elements of (1) the trend of Meth. abuse, (2) the impact of Meth abuse, and (3) behavioural contradictions of Meth abuse with self-rationalized thinking. As a conclusion, this present study illustrated attention to the urgent need to strengthen existing intervention programs, drug policies, and professional supports, or to devise improved ones, with the aim of reducing Meth. abuse in Malaysia.